2015
DOI: 10.3945/ajcn.114.104893
|View full text |Cite
|
Sign up to set email alerts
|

Adequate enteral protein intake is inversely associated with 60-d mortality in critically ill children: a multicenter, prospective, cohort study

Abstract: Background: The impact of protein intake on outcomes in pediatric critical illness is unclear. Objective: We examined the association between protein intake and 60-d mortality in mechanically ventilated children. Design: In a prospective, multicenter, cohort study that included 59 pediatric intensive care units (PICUs) from 15 countries, we enrolled consecutive children (age: 1 mo to 18 y) who were mechanically ventilated for $48 h. We recorded the daily and cumulative mean adequacies of energy and protein del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(178 citation statements)
references
References 33 publications
2
167
1
8
Order By: Relevance
“…Study methods have been previously described [11] and were the identical for two surveys [12]. Site investigators in participating PICUs with 8 or more beds collected demographic, clinical, and nutritional data on consecutively admitted mechanically ventilated children aged 1 month to 18 years with an expected stay of 3 or more days.…”
Section: Methodsmentioning
confidence: 99%
“…Study methods have been previously described [11] and were the identical for two surveys [12]. Site investigators in participating PICUs with 8 or more beds collected demographic, clinical, and nutritional data on consecutively admitted mechanically ventilated children aged 1 month to 18 years with an expected stay of 3 or more days.…”
Section: Methodsmentioning
confidence: 99%
“…Data were prospectively collected as part of the second Pediatric International Nutrition Study (PINS2) with VAP as an a priori identified outcome. Participation, recruitment and data collection methods for the PINS2 study have been previously reported (9). In brief, participating sites recruited consecutive subjects, age 1 month to 18 years, who required mechanical ventilation and had an anticipated PICU stay >48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Early initiation of adequate enteral feeds in critical illness is linked to a decrease in short-term and long-term mortality 25. This is especially important in AKI as children are in a highly catabolic state, potentially contributing to further metabolic derangement, including uraemia.…”
Section: Stec-hus (Formally D+hus)mentioning
confidence: 99%